2022
DOI: 10.25122/jml-2021-0374
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of malaria epidemiological trend in Kermanshah province, Iran, 1986–2014

Abstract: Malaria is the most severe protozoan disease in the world. As a result of strict malaria control programs, malaria's epidemiological model has changed. Knowing this epidemiological model and its effects will help us predict and prevent a new epidemic. This research was conducted to review the epidemiological trend of malaria in the Kermanshah province of Iran and some of its effective factors. Data were extracted from the registers in the disease control unit of the province, national population census, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…According to the results, the majority of malaria cases during the study period were observed in young and middle-aged individuals. This aligns with previous studies which also reported a higher prevalence of the disease in people aged 15 and above (20). According to the gender ratio of patients in the province, as in all previous studies (5), men are more likely to be affected by this disease than women (82.9% versus 17.1%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the results, the majority of malaria cases during the study period were observed in young and middle-aged individuals. This aligns with previous studies which also reported a higher prevalence of the disease in people aged 15 and above (20). According to the gender ratio of patients in the province, as in all previous studies (5), men are more likely to be affected by this disease than women (82.9% versus 17.1%).…”
Section: Discussionsupporting
confidence: 91%
“…This nding is consistent with other studies conducted in Iran, where that type of parasite was also found to be the dominant species. For instance, in studies conducted in Kermanshah and Mazandaran, Plasmodium vivax accounted for 98% of all cases (20,25). Similarly, in the Kanarak study, Plasmodium vivax accounted for 91.5% of the cases, and in the Razavi Khorasan study, it accounted for 96.4% of the cases (27).…”
Section: Discussionmentioning
confidence: 99%
“…In 1951 a comprehensive programme for eradication of malaria was initiated in Iran, and in 1985 it changed to malaria control because of the restrictions and challenges ( 2 ). This country has been in the malaria elimination phase since 2010 and is aiming to become entirely malaria-free by 2025 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%